Human Capital Development and Macroeconomic Performance in Nigeria: An Autoregressive Distributed Lag (ARDL) Approach - Olukayode Emmanuel Maku; Emmanuel Ogbonna Ajike; Solomon Chimereze Chinedu (ETIKONOMI, 2019)
Developed nations continue to invest heavily in the development and training of their human resources. Huge budgetary allocations show it to education and health, yet Nigeria’s human capital development policy has only been effective on paper. This study examined the impact of human capital development on the macroeconomic performance of Nigeria. Using the autoregressive distributed lagged (ARDL) model, this study shows an insignificant negative relationship between human capital development and per capita GDP in the short run. The results also showed that only the tertiary enrolment rate significantly and positively improved per capita GDP within the period under review. The study concluded that the government’s efforts aimed at boosting human capital have been insufficient.JEL Classification: O47, J11, J24